How Covid-19 has impacted global consumer behaviours and the adoption of digital business strategies by companies in the UK (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study sought to establish how different facets of consumer behaviour have been affected bythe Covid-19 pandemic, and how companies in the UK have adopted digital strategies to copewith the challenges that the pandemic has brought about. A desk-based research approach wasused. It relied on a wide range of secondary sources such as books, journal articles andpublications made by experts in the field of business and consumer behaviour. The main findingsfrom the research highlight a shift of consumer behaviour, increasing the tendency of makingonline purchases except for essential commodities that have to be physically purchased. Thisshift has triggered a corresponding increase in adoption of digital technologies for businesses toensure that they continue making sales amidst lockdowns and movement restrictions. The Covid-19 pandemic is quite a recent phenomenon and its impacts on consumer behaviour have beenexplored for just more than a year before this study. Therefore, the long-term impacts may nothave been properly documented. Previous studies that were relied upon also had differentobjectives from this study and as such could impact the accuracy with which this study’sobjectives were met. Through analysis of previous studies, this study has provided a newinterpretive perspective to existing research on the impact of Covid-19 to consumer behaviourand digital adoption by businesses. It provides valuable insights on how businesses can embracedigital strategies to maintain their relevance to clientele even as their consumer behaviourschange.